Molecular genetic system for regenerative studies using newts. (11th January 2013) - Hayashi, Toshinori; Yokotani, Naoki; Tane, Shoji; Matsumoto, Akira; Myouga, Ayumi; Okamoto, Mitsumasa; Takeuchi, Takashi
<x xml:space="preserve">Abstract</x> Urodele newts have the remarkable capability of organ regeneration, and have been used as a unique experimental model for more than a century. However, the mechanisms underlying regulation of the regeneration are not well understood, and gene functions in particular remain largely unknown. To elucidate gene function in regeneration, molecular genetic analyses are very powerful. In particular, it is important to establish transgenic or knockout (mutant) lines, and systematically cross these lines to study the functions of the genes. In fact, such systems have been developed for other vertebrate models. However, there is currently no experimental model system using molecular genetics for newt regenerative research due to difficulties with respect to breeding newts in the laboratory. Here, we show that the Iberian ribbed newt (Pleurodeles waltl) has outstanding properties as a laboratory newt. We developed conditions under which we can obtain a sufficient number and quality of eggs throughout the year, and shortened the period required for sexual maturation from 18 months to 6 months. In addition, P. waltl newts are known for their ability, like other newts, to regenerate various tissues. We revealed that their ability to regenerate various organs is equivalent to that of Japanese common newts. We also developed a method for efficient transgenesis. These studies demonstrate that P. waltl newts are a suitable model animal for analysis of regeneration using molecular genetics. Establishment of this experimental model will enable us to perform comparable studies using these newts and other vertebrate models.